THE EFFECT OF THYROXINE (T4) HORMONE TREATED BY IMMERSION TOWARD THE GROWTH AND SURVIVAL RATE ASIAN REDTAIL CATFISH JUVENILE (Hemibagrus nemurus) - Mezzi Dayuni; Niken Ayu Pamukas; Mulyadi Mulyadi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACK            This research was conducted on August 2018 until September2018 at Aquaculture Technology Laboratory of Fisheries Faculty and Marine, University Riau Pekanbaru. The purpose of this experiment was to determine the optimal dose of Thyroxine hormone (T4) treated by immersion on the growth and survival rate of Asian redtail catfish juvenile (Hemibagrus nemurus). The research method used in this study was an experimental method and completely randomized design with four treatments and three replication. The treatmens in this study were control P0 (without thyroxine hormone), P1 (soaking with hormone thyroxine at a dose 0.25 mg / litre), P2 (soaking with hormone thyroxine at a dose of 0.50 mg /litre), P3 (soaking with hormone thyroxine at a dose of 0,75 mg / litre). The best result was treatment on soaking treatment with hormone thyroxine 0,75 mg/litre with absolute growth weight 6.66 g, absolute growth length 5,6 cm, specific growth rate 3,43%, the highest feed efficiency 119,62 %, and feed conversion 0,84 and survival rate 100%.Water quality range at all treatments were: the temperature ranges was from 28 to 29,70C, pH ranges was from 6.8 to 7,3, and DO ranges was from 4.0 to 5,6 mg/L and ammonia was around 0,00151-0,00803 mg/L respectifely.Keyword: Thyroxine (T4), Hemibagrus nemurus, immersion